Analisis Penentuan Komoditi Unggulan Pada Sub Sektor Tanaman Pangan Dan Hortikultura Dikecamatan Harau - Siregar, Nurhawani; Alfikri; Veronice (Indonesian Journal of Islamic Economics and Business, 2025)
Lima Puluh Kota Regency has significant capacity in the agricultural sector for food crops, but this potential has not been fully utilized to drive local economic development. This study aims to determine the leading commodities in the food crops and horticulture sub-sectors in Lima Puluh Kota Regency by utilizing the Location Quotient (LQ) as a method. The data used in this study include the production value and prices of agricultural products from 2019 to 2023. It is hoped that the results of this analysis will provide suggestions regarding commodities that have high economic value production and must be given superior priority with superior commodities such as lowland rice, corn, cassava, shallots, eggplant, cucumbers in regional development. Identification of these leading sectors will be the basis for formulating policies that support increased productivity in agriculture and sustainable regional economic growth.